Phenytoin Loading Doses in Adult Critical Care Patients: Does Current Practice Achieve Adequate Drug Levels?. Issue 5 (September 2013) - Putt, M. T.; Udy, A. A.; Jarrett, P.; Martin, J.; Hennig, S.; Salmon, N.; Lipman, J.; Roberts, J. A.
Phenytoin is regularly employed in the critically ill for prophylaxis against or treatment of seizure disorders. No prior studies have examined current dosing practices in an Australasian intensive care unit (ICU) setting. The aims of this study were to: a) describe the adequacy of contemporary dosing in respect to free and total serum phenytoin concentrations; b) identify factors associated with therapeutic drug concentrations; and c) examine the accuracy of predictive equations that estimate free concentrations in this setting. All patients receiving a loading dose of phenytoin in a tertiary-level ICU were eligible for enrolment; 53 patients were enrolled in the study. Serum samples to determine free and total phenytoin concentrations (measured by high performance liquid chromatography) were then drawn prior to the following dose. Free concentrations below the recommended target (<1 mg/1) were considered as suboptimal. The most common indication for phenytoin loading was traumatic brain injury (49%) and the mean administered dose was 14.5 (3.66) mg/kg. Twenty-six patients (49%) had suboptimal trough free concentrations, although this subgroup was significantly heavier and therefore received a lower per kilogram dose (12.8 [3.1] vs 16.3 [3.4] mg/kg, P =0.001). In multivariate analysis, larger weight adjusted doses ( P =0.018), higher albumin concentration ( P =0.034) and receiving phenytoin for an indication other than seizure ( P =0.035), were associated with a greater likelihood of adequate concentrations. In conclusion, phenytoin dosing remains complex in critically ill patients, although lower per kilogram loading doses are strongly associated with free concentrations below the desired target.